Penguatan Profil Pelajar Pancasila dalam Upaya Meminimalisir Bullying di Sekolah Dasar - Wahyu Adi Setiawan; Arief Cahyo Utomo (Elementary Teacher Education Program, Majalengka University, 2024)
This research aims to describe the importance of strengthening the Pancasila Student Profile in an effort to anticipate bullying problems among fifth grade students. This research was conducted at SDN Banyurip 1. This research method uses descriptive qualitative where the main focus is on observing the strengthening of the Pancasila Learner Profile, the class observed is class V. The data collection techniques used were interviews, observations, and documentation. The data collection techniques used are interviews, observation, and documentation. The interview used is semi-structured, in its implementation it is more free when compared to structured interviews. Researchers carried out non-participant observation data collection. Researchers obtained documents in the form of project modules to strengthen the Pancasila Student Profile, school profiles, teacher data, and student data. Data analysis conducted by researchers is divided into three flows, namely (1) data reduction; (2) data presentation; and (3) conclusion drawing. The results showed that the strengthening of the Pancasila Learner Profile at Banyurip 1 State Elementary School was implemented in the form of the Pancasila Learner Profile Strengthening Project (P5) and School Habituation Culture by means of character building. Through the formation of noble character and courtesy, students can understand that humans as creatures who need each other should always maintain harmony and peace. Therefore, strengthening the Pancasila Student Profile can anticipate and minimize the occurrence of bullying behavior at SDN Banyurip 1.